The effect of aloe vera extract in vivo on spermatozoa quality of sprague dawley rats - Endang Purwaningsih; Samsul Mustofa; Marisa Riliani (Fakultas Peternakan Universitas Papua, 2026)
Aloe vera can act as an anti-fertility agent or increase fertility depending on dose, preparation and gender. Several studies have been carried out using a variety of doses in vitro and in vivo in both humans and animals experimental regarding the effect of Aloe vera on the quality of spermatozoa. Currently research on Aloe vera's effects on the reproductive system, particularly sperm quality, is still limited.This study aims to determine the effect of Aloe vera extract on the sperm quality of Sprague Dawley rats. This research is pure experimental with a randomized block design, for 6 months Population and research subjects are male white rats Sprague-Dawley strain, aged 10 – 12 weeks. The sample in this study was part of the population that met the inclusion and exclusion criteria, as many as 24 individuals and divided into 4 groups, namely the control group (K) and 3 treatment groups with Aloe vera extract (PI, a dose of 150 mg/kgBW; PII, a dose of 200 mg/kgBW, and PIII, a dose of 250 mg/kgBW) as the independent variable. The dependent variables were the quality parameters of spermatozoa, specifically including sperm density, sperm motility, sperm viability determined and sperm membrane integrity. The data was statistically processed using the ANOVA Test and Kruskal Wallis. The results showed that the administration of Aloe vera extract significantly increased spermatozoa motility (Mean=49.2; SD=23.7; p<0.05) and viability (Mean=61.7, SD=22.6; p < 0.05) in a dose-dependent manner. The overall increase in motility ranged from 59% to 144%, while viability improved by 14% to 61% across treatment groups compared to controls. The increase in density and integrity of spermatozoa membranes was not significant (p > 0.05). It was concluded that Aloe vera extract could improve the sperm quality of Sprague Dawley rats.